Pengaruh Ekstrak Etanol Biji Pepaya (Carica papaya L.) Terhadap Pertumbuhan Tanaman Cabai (Capsicum annuum L.) - Husna Fadilla; Yulianty; Sri Wahyuningsih; Endang Nurcahyani (CV. Multi Kreasi Media, 2026)
The large red chili pepper plant (Capsicum annuum L.) is a vegetable crop. Demand for chili peppers continues to rise every year. This has led to increased market demand, making it necessary to take steps to boost productivity. One strategy for enhancing chili pepper plant growth involves the use of plant extracts.papaya seeds (Carica papaya L.) are known to contain secondary metabolites that can help protect plants from environmental stress and promote plant growth. This study aims to determine the effect of papaya seed ethanol extract on the growth of large red chili plants and to identify the optimal concentration of papaya seed ethanol extract for enhancing the growth of large. red chili plants. The study was conducted using a Completely Randomized Design (CRD) with papaya seed extract (Carica papaya L.) as the single factor, consisting of 4 concentration levels: 0%, 1%, 2%, and 3%, with 6 replicates. The observed parameters were germination percentage, plant height, root length, number of leaves, and chlorophyll content. The data were analyzed using analysis of variance (ANOVA) and a 5% BNJ test. The results showed that the best concentration was P1 (1%) because it increased plant height on the 28th day after sowing. The other parameters did not show a significant effect. red chili plants.